2019
DOI: 10.7554/elife.48629
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin and dynein use distinct mechanisms to bypass obstacles

Abstract: Kinesin-1 and cytoplasmic dynein are microtubule (MT) motors that transport intracellular cargoes. It remains unclear how these motors move along MTs densely coated with obstacles of various sizes in the cytoplasm. Here, we tested the ability of single and multiple motors to bypass synthetic obstacles on MTs in vitro. Contrary to previous reports, we found that single mammalian dynein is highly capable of bypassing obstacles. Single human kinesin-1 motors fail to avoid obstacles, consistent with their inabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 48 publications
4
54
0
Order By: Relevance
“…Intriguingly, these linear motor proteins do not always follow a strictly linear path along actin filaments or microtubules (MTs). They also produce force perpendicular to their direction of movement, generating sidesteps or off-axis movement along their filamentous tracks (Ricca & Rock, 2010;Brunnbauer et al, 2012;Ferro et al, 2019). Torque generation of motor proteins was first demonstrated by the purified Tetrahymena axonemal dynein, which rotates the microtubules around their axes while translocating them (Vale & Toyoshima, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, these linear motor proteins do not always follow a strictly linear path along actin filaments or microtubules (MTs). They also produce force perpendicular to their direction of movement, generating sidesteps or off-axis movement along their filamentous tracks (Ricca & Rock, 2010;Brunnbauer et al, 2012;Ferro et al, 2019). Torque generation of motor proteins was first demonstrated by the purified Tetrahymena axonemal dynein, which rotates the microtubules around their axes while translocating them (Vale & Toyoshima, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Torque generation of motor proteins was first demonstrated by the purified Tetrahymena axonemal dynein, which rotates the microtubules around their axes while translocating them (Vale & Toyoshima, 1988). Subsequently, in vitro studies revealed that such torsional and axial force generation appears to be a prevalent feature for all three families of molecular motors (Nishizaka et al, 1993;Yajima & Cross, 2005;Beausang et al, 2008;Yajima et al, 2008;Ricca & Rock, 2010;Brunnbauer et al, 2012;Can et al, 2014;Ferro et al, 2019). However, it remains unclear whether motor proteins take sidesteps and generate torque in a living cell.…”
Section: Introductionmentioning
confidence: 99%
“…Microtubule surfaces in cells are crowded by numerous microtubule-associated proteins, which act as obstacles for processively moving molecular motors. When kinesin-1 encounters an obstacle, its run length decreases as kinesin-1 is more likely to dissociate from the microtubule 30,49 than to continue its run by switching the protofilaments by side-stepping and circumventing the obstacle 31 . In vitro single molecule experiments in cell lysate imitate the physiological state of microtubules crowded with microtubule associated proteins 30,59 , while rigor-binding kinesin-1 mutants provide static roadblocks masking the kinesin-1 binding sites 31 .…”
Section: Discussionmentioning
confidence: 99%
“…7 The microtubule surface in cells is crowded with numerous microtubule-associated proteins hindering the motion of molecular motors. Crowding of the microtubule surface results in a drastic shortening of the run length of kinesin-1 30,31,49,50 . Since we observed that TRAK1 increased the processivity of KIF5B, we wondered whether TRAK1 can extend the movement range of kinesin-1 in crowded conditions.…”
Section: Trak1 Increases the Processivity Of Kif5bmentioning
confidence: 99%
“…Microtubules are essential for maintaining the cell shape, polarity, migration and division [ 5 ]. Furthermore, they are utilized by protein motors kinesins and dyneins to transport molecules inside a cell [ 8 ].…”
Section: Microtubule Inhibitorsmentioning
confidence: 99%